Atomic-scale insight into the enhanced surface stability of methylammonium lead iodide perovskite by controlled deposition of lead chloride. Issue 8 (14th July 2021) - Jamshaid, Afshan; Guo, Zhendong; Hieulle, Jeremy; Stecker, Collin; Ohmann, Robin; Ono, Luis K.; Qiu, Longbin; Tong, Guoqing; Yin, Wanjian; Qi, Yabing
Abstract : Our scanning tunneling microscopy and density functional theory studies show that the Cl incorporation plays a crucial role in the surface stability of the metal halide perovskite CH3 NH3 PbI3 . Abstract : The incorporation of a certain amount of Cl ions into methylammonium lead iodide (MAPbI3 ) perovskite films and how these incorporated Cl ions affect the structural and electronic properties of these films have been an intensively studied topic. In this study, we comprehensively investigated Cl incorporation in MAPbI3 at the atomic scale by a combined study of scanning tunneling microscopy, X-ray photoelectron spectroscopy, ultraviolet and inverse photoemission spectroscopy, density functional theory and molecular dynamics calculations. At a Cl concentration of 14.8 ± 0.6%, scanning tunneling microscopy images confirm the incorporation of Cl ions on the MAPbI3 surface, which also corresponds to the highest surface stability of MAPbI3 found from the viewpoint of both thermodynamics and kinetics by density functional theory and molecular dynamics calculations. Our results show that the Cl concentration is crucial to the surface bandgap and stability of MAPbI3 .